Seville in the Urban System of Andalusia during the Late Middle Ages (SP) (Edad Media. Revista de Historia, 2017)
Against the backdrop of medieval Andalusia’s urban settings, this paper relies on several perspectives to analyse the central and hierarchical role played by the city of Seville in the whole Kingdom of the same name—particularly with regard to other towns and cities. Among the factors that influenced that process, special mention must be made of Seville’s granting of its fuero to those towns and cities; the jurisdictional scope of its local council; the fact that a number of public officials with regional and even supraregional jurisdiction were stationed there; Seville’s role in defending the Kingdom’s frontiers; and the city’s status as head of tax districts, main centre for the regulation of economic activities, seat of the archbishop and capital of the seigneurial domain. All these factors furthermore promoted the circulation of people, information, crafts, etc, and ultimately exerted their influence on the artistic and cultural fields.
Keywords: Seville. Late Middle Ages. Towns. Urban History. Urban centrality.